2011
DOI: 10.1007/s13105-011-0106-2
|View full text |Cite
|
Sign up to set email alerts
|

Dietary n-3 polyunsaturated fatty acids modify fatty acid composition in hepatic and abdominal adipose tissue of sucrose-induced obese rats

Abstract: The fatty acid profile of hepatocytes and adipocytes is determined by the composition of the dietary lipids. It remains unclear which fatty acid components contribute to the development or reduction of insulin resistance. The present work examined the fatty acid composition of both tissues in sucrose-induced obese rats receiving fish oil to determine whether the effect of dietary (n-3) polyunsaturated fatty acids (PUFAs) on the reversion of metabolic syndrome in these rats is associated to changes in the fatty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
3
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 38 publications
3
3
0
Order By: Relevance
“…Interestingly, linoleic acid was significantly increased in MG and FG rats compared to CG rats. These results are also in line with a previous study, which showed that dietary n‐3 polyunsaturated fatty acids modify the fatty acid composition, especially linoleic acid content, in the abdominal adipose tissue of sucrose‐induced obese rats . Other fatty acid contents remained unchanged between experimental groups.…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…Interestingly, linoleic acid was significantly increased in MG and FG rats compared to CG rats. These results are also in line with a previous study, which showed that dietary n‐3 polyunsaturated fatty acids modify the fatty acid composition, especially linoleic acid content, in the abdominal adipose tissue of sucrose‐induced obese rats . Other fatty acid contents remained unchanged between experimental groups.…”
Section: Resultssupporting
confidence: 86%
“…wileyonlinelibrary.com/jsfa These results are also in line with a previous study, which showed that dietary n-3 polyunsaturated fatty acids modify the fatty acid composition, especially linoleic acid content, in the abdominal adipose tissue of sucrose-induced obese rats. 50 Other fatty acid contents remained unchanged between experimental groups. The total amounts of monounsaturated fatty acids and PUFAs were significantly elevated in MG and FG rats, compared with CG rats.…”
Section: Tissue Fatty Acid Compositionmentioning
confidence: 91%
“…ab P < 0.05 indicates difference from week 1, 5 and 10, compared with the control group As shown in Fig. 1, the These results are consistent with those reported by Aguilera et al, who used similar concentrations of sucrose in drinking water and observed increased abdominal fat, dyslipidemia and high levels of tumor necrosis factor alpha (TNF) 31 .…”
Section: Liquid Consumption and Food And Caloric Intake In Sucrose-fesupporting
confidence: 89%
“…It has been suggest that these results provide a rational basis for the use of EPA and DHA as an alternative treatment for patients with metabolic syndrome (Castro et al 2015). It is known that n-3 PUFA incorporation in phospholipid membranes is linked to modulation of tissues' insulin response (Calder 2012), a fact that can be related to plasma triglyceride content reduction (Yamazaki et al 2011;Alexander-Aguilera et al 2011). Furthermore, the n-3 PUFAs can modulate the activity of peroxisome proliferator activated receptors (PPARs), transcriptions factors that control the expression of genes involved in lipid and glucose metabolism (Ferreira et al…”
Section: R a F Tmentioning
confidence: 99%